Concise Exposure and Damage Indicators for Predicting Foreseeable Effects Of Work-Related Upper Limb Disorders - SA Moussavi- Najarkola (Tehran University of Medical Sciences, 2006)
Since work-related musculoskeletal disorders (WMSDS) have a high prevalence in different industries, in order to quantify the prevalence of WMSDS of the upper limbs in of exposed group and find a relationship between exposure indices and effect indicators, this research was carried out. A total of 404 male exposed and of 120 male non-exposed workers of Qaemshahre (northern Iran) weaving factory located in the north of Iran were studied. Regarding the quantification of exposure, use was made of the Occupational Repetitive Actions (OCRA). Also the Concise Damage Index (CDI) was calculated for any job and then statistically significant relationships between CDI and OCRA exposure indices were surveyed. It was considered that there were significant associations between OCRA and an effect indicators (CDI) represented by the prevalence of all the WMSDS of the upper limbs (R2= 0.85, P=0.001). When a logarithmic conversion of the relative exposure (OCRA) and injury indices was carried out, a simple and multiple linear regression model resulted that seems to provide a satisfactory and truly predictive performance of the risk of WMSDS of the upper limbs based on the exposure index, length of time, lack of recovery periods, and etc.